2016
DOI: 10.1038/srep33121
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the dual-specificity protein kinase TTK as a therapeutic target for intrahepatic spread of liver cancer

Abstract: Therapies for primary liver cancer, the third leading cause of cancer-related death worldwide, remain limited. Following multi-omics analysis (including whole genome and transcriptome sequencing), we were able to identify the dual-specific protein kinase TTK as a putative new prognostic biomarker for liver cancer. Herein, we show that levels of TTK protein are significantly elevated in neoplastic tissues from a cohort of liver cancer patients, when compared with adjacent hepatic tissues. We also tested the uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…A lack of Mps1 perturbs centrosome duplication (Fisk et al, 2003) (Continued) BJP M Choi et al Santaguida et al, 2010;Dou et al, 2015), a failure to correct erroneous microtubule attachment (Jelluma et al, 2008), cytokinesis failure (Fisk et al, 2003) and apoptosis (Jemaa et al, 2016), shortens mitosis (Dou et al, 2015;Jemaa et al, 2016), and prevents the recruitment of SAC-related proteins, including Mad1, Mad2, Bub1, BubR1 and RodZw10-Zwilch (Martin-Lluesma et al, 2002;Santaguida et al, 2010;Jemaa et al, 2016). In addition, depletion of (Hewitt et al, 2010) Chromosome misalignment (Dou et al, 2015) Failure in recruitment of Mad1, Mad2, Bub1 and CENP-E (Hewitt et al, 2010) Short mitotic duration (Hewitt et al, 2010;Gurden et al, 2015) Apoptosis (Jemaa et al, 2016) BAY 1161909 0.34 nM (Wengner et al, 2016) Breast, lung and ovarian cancer (Wengner et al, 2016) Phase I ClinicalTrials.gov ID: NCT02138812 BAY 1217389 0.63 nM (Wengner et al, 2016) Phase I ClinicalTrials.gov ID: NCT02366949 CFI-402257 1.7 nM (Liu et al, 2016) MPI-0479605 1.8 nM (Tardif et al, 2011) Chromosome missegregation Colon cancer (Tardif et al, 2011) Hyperploidy Apoptosis Up-regulation of p53, p21 and γ-H2AX (Tardif et al, 2011) continues Effect of Mps1 inhibitor on hepatocellular carcinoma cells BJP Mps1 inhibits proliferation of HCC cells (Liang et al, 2014;Liu et al, 2015;Miao et al, 2016). Overall, because the dysregulation of Mps1 leads to an accumulation of chromosomal instabilities and, finally, cell death, it may be a target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of Mps1 perturbs centrosome duplication (Fisk et al, 2003) (Continued) BJP M Choi et al Santaguida et al, 2010;Dou et al, 2015), a failure to correct erroneous microtubule attachment (Jelluma et al, 2008), cytokinesis failure (Fisk et al, 2003) and apoptosis (Jemaa et al, 2016), shortens mitosis (Dou et al, 2015;Jemaa et al, 2016), and prevents the recruitment of SAC-related proteins, including Mad1, Mad2, Bub1, BubR1 and RodZw10-Zwilch (Martin-Lluesma et al, 2002;Santaguida et al, 2010;Jemaa et al, 2016). In addition, depletion of (Hewitt et al, 2010) Chromosome misalignment (Dou et al, 2015) Failure in recruitment of Mad1, Mad2, Bub1 and CENP-E (Hewitt et al, 2010) Short mitotic duration (Hewitt et al, 2010;Gurden et al, 2015) Apoptosis (Jemaa et al, 2016) BAY 1161909 0.34 nM (Wengner et al, 2016) Breast, lung and ovarian cancer (Wengner et al, 2016) Phase I ClinicalTrials.gov ID: NCT02138812 BAY 1217389 0.63 nM (Wengner et al, 2016) Phase I ClinicalTrials.gov ID: NCT02366949 CFI-402257 1.7 nM (Liu et al, 2016) MPI-0479605 1.8 nM (Tardif et al, 2011) Chromosome missegregation Colon cancer (Tardif et al, 2011) Hyperploidy Apoptosis Up-regulation of p53, p21 and γ-H2AX (Tardif et al, 2011) continues Effect of Mps1 inhibitor on hepatocellular carcinoma cells BJP Mps1 inhibits proliferation of HCC cells (Liang et al, 2014;Liu et al, 2015;Miao et al, 2016). Overall, because the dysregulation of Mps1 leads to an accumulation of chromosomal instabilities and, finally, cell death, it may be a target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…TTK has been considered to be dysregulated in various cancer cells because TTK dysregulation causes excess centrosomes resulting in aberrant mitotic spindles. Reduced in TTK level or activity in tumors can lead to a decrease of cell viability and division; thus, inhibition of TTK has been regard as an attractive target for anti-cancer drug development [6][7][8]. TTK has been also reported that upregulation of TTK increases lung cancer progression due to X-linked deubiquitinase USP9X dysfunction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For mechanistic studies in vitro, human HepG2 cells were analysed for expression patterns of adenosine receptors and ectoenzymes by qPCR and Western blot, as previously described . Extracellular adenosine metabolism was detected by thin layer chromatography (TLC) as previously established in the laboratory .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were also treated with adenosine (50 µmol/L) for various times, in the presence or absence of 8‐(3‐Chlorostyryl)‐caffeine (CSC, 60 nmol/L; a xanthine and an A2A antagonist), or alloxazine (50 µmol/L; an A2B antagonist). Cell growth was determined using Cell Counting Kit‐8 and metastatic potential was examined by soft agar 3D colony formation assay as reported recently . Alterations in key adenosine‐mediated cancer pathways inclusive of MAPK (ERK and JNK) and NF‐kappa B were evaluated by Western blot.…”
Section: Methodsmentioning
confidence: 99%